Evaluation of Clinical Features And Outcome Of Ectopic Pregnancy (Journal of Dhaka National Medical College & Hospital, 2021)
Background: An ectopic pregnancy occurs outside the uterus and is a relatively common condition among women of childbearing age. Most ectopic pregnancies occur in the Fallopian tube (so-called tubal pregnancies), but implantation can also occur in the cervix, ovaries, and abdomen.Objective: To evaluate different presentation and outcome of ectopic pregnancy.Material and Methods: This study was undertaken among the patients admitted in the Department of Obstetrics and Gyrtaecology, Dhaka National Medical College Hospital, Dhaka during the period from October 2017 to March 2018. Clinical evaluation of cases of ectopic pregnancy in terms of sociodemographic factors, presentations, risk factors, examination findings, per operative findings and management offered to the patients.Results: Most of the patients were 20-30 years age group and mean age was 28.08±4.24 years. Commonest presentation was lower abdominal pain (94%), amenorrhoea (100%), P/V bleeding (38%) and syncopal attack (48%). Previous history of abortion/MR (50%), history of pelvic infection (30%) and history of D&C (16%) constitute the main bulk of risk factors. Most of the patients managed by laparotomy followed by salpingectomy which is still the standard treatment in many cases.Conclusion: Study has found that previous abortions are major etiological factor for ectopic pregnancy than previous pelvic infection. Most of the patients were managed by laparotomy. The general public should be made aware the sign and symptoms of ectopic pregnancy. Proper and modern diagnostic tools and training programme for these should be made available in all tertiary level hospital.J. Dhaka National Med. Coll. Hos. 2021; 27 (02): 30-34